2020
DOI: 10.3390/molecules26010075
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Deep Eutectic Solvents to Reduce the Release of Hazardous Gases to the Atmosphere: A Critical Review

Abstract: The release of certain gases to the atmosphere is controlled in many countries owing to their negative impact on the environment and human health. These gases include carbon dioxide (CO2), sulfur oxides (SOx), nitrogen oxides (NOx), hydrogen sulfide (H2S) and ammonia (NH3). Considering the major contribution of greenhouse gases to global warming and climate change, mitigation of these gases is one of the world’s primary challenges. Nevertheless, the commercial processes used to capture these gases suffer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 147 publications
0
18
0
Order By: Relevance
“…Similar works considering H 2 S are less diffuse. Shah et al (2017) [32] screened ionic liquids for H 2 S absorption, while Wazeer et al 2021 [33] reviewed recent results on capture of hazardous gases (NH 3 , SO x , NO x and H 2 S) using different types of deep eutectic solvents.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar works considering H 2 S are less diffuse. Shah et al (2017) [32] screened ionic liquids for H 2 S absorption, while Wazeer et al 2021 [33] reviewed recent results on capture of hazardous gases (NH 3 , SO x , NO x and H 2 S) using different types of deep eutectic solvents.…”
Section: Methodsmentioning
confidence: 99%
“…When an IL is one of the components in DESs, the advantages of DESs over ILs disappear [171]. Wazeer et al (2021) [33] reviewed recent results on capture of acid gases using different types of DESs and confirmed the lack of research on H 2 S capture through DES.…”
Section: H 2 S and Co 2 Capturementioning
confidence: 96%
See 1 more Smart Citation
“…CO 2 capture is one application that can benefit from DES. Existing studies have demonstrated the potential of DES for CO 2 capture ( Krishnan et al, 2020 ; Song et al, 2020 ; Wazeer et al, 2021a ; Wazeer et al, 2021b ). However, most studies investigating CO 2 capture in DES proposed using ionic DES, which has the same drawbacks as those related to IL, especially in terms of hygroscopicity.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17] The applications of DESs as carbon capture materials have also been extensively investigated in recent years, 18,19 and DESs that can chemically capture CO 2 attract great interest from researchers due to their high CO 2 capacities. [20][21][22][23][24] Zhang et al studied the CO 2 capture by DESs composed of MEA and an ionic liquid (IL) 1-butyl-3-methylimidazolium chloride ([Bmim][Cl]), in which CO 2 was captured through the reaction between CO 2 and the amino group of MEA. 25 Trivedi et al found that DESs formed by HBDs ethylenediamine (EDA) and monoethanolammonium chloride ([MEAH][Cl]) exhibited high CO 2 capacities due to the reaction between CO 2 and EDA.…”
mentioning
confidence: 99%